Spectactorial Sisterhood: Relasi Sosial Pengguna Second Account di Instagram - Amelia Rugun Sirait (Antropologi Indonesia, 2021)
Instagram is a popular image based social media platform. Usually, users have their own accounts for their personal profile to be viewed publicly. As Instagram features develop, users may have more than one account. Accounts that are specific to certain circle of friends are called “second accounts” and treated as private accounts used to express and relate through images. In this social media ethnography, seven subjects shared their experiences through uploaded images, videos and texts. They have the awareness to avoid relationships and gazes in their main account by building a different subjectivity in their second account. Contents on their second account are stories shared with their most trusted people. The dynamics of second account show different relations expressed through visual cues in Instagram, which I will call “spectatorial sisterhood” here.